Effect on source signal condition for pyramidal microwave absorber performance - Nornikman, Hassan; Fareq, Malek, Dr.; Soh, Ping Jack (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/